Pengaruh Current Ratio, Return on Assets dan Debt to Equity Ratio terhadap Dividend Payout Ratio Perusahaan Manufaktur - I Yensi Godchild Nehe; Dimas Sumitra Danisworo; Rochmi Widayanti (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aim to finds out the influence of Current Ratio, Return On Assets and Debt to Euity Ratioon Dividend Payout Ratio in mmaufacturing companies on the Indonesia stock exchange in 2011-2020. The data used in this study were obtained from the annual financial reports published on the indonesia stock exchange (IDX). After passing the purposive sampling stage, the sample that can be used is 3 companies. The method of analysis used in this research is multiple linear regression analysis which is processed using the SPSS version 24 program. The result of this study indicate that the variable Current Ratio (CR)and Return On Asset (ROA) partially have an insignificant negative effect on the Dividend Payout Ratio (DPR), while the Debt to Euity Ratio (DER) variable has a significant positive effect on the Dividend Payout Ratio(DPR). And Current Ratio (CR), Return On Asset (ROA), and Debt to Euity Ratio (DER) simultaneously affect the Dividend Payout Ratio (DPR) in manufacturing companies listed on the Indonesia stock Ezchange for the 2011-2020 period. Keywords : Current Ratio, Return On Asset, Debt to Euity Ratio, Dividend Payout Ratio.